Enhancing Students’ Climate Change Literacy through Climate-Integrated Physics Learning via Citizen Science - Kuntari, Diyah Ayu; Ristanto, Sigit; Siswanto, Joko (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to evaluate the effectiveness of climate change-integrated physics learning using a citizen science approach in improving the Climate Change Literacy (CCL) of grade XI high school students. A quantitative research method with a one-group pretest-posttest design was employed. Data were collected through cluster random sampling using test instruments and observation sheets to monitor learning implementation and student participation. The analysis included normality, homogeneity, and paired t-tests to assess significant differences between pretest and posttest scores. The findings revealed significant improvements in students’ CCL across cognitive, affective, and behavioral domains, with posttest scores showing statistically significant gains and 100% mastery achievement. This study provides empirical evidence supporting the integration of global issues into science education and offers valuable insights for curriculum development aimed at fostering climate awareness and literacy among youth.